Konsep Pendidikan Karakter dalam Kitab Ta`Limul Muta`Aallim Karya Imam Az-Zarnuji dan Relevansinya Terhadap Kurikulum Merdeka Belajar - Nurullah Nurullah; Asrorudin Asrorudin (LPPM STAIS Dharma Indramayu, 2022)
Education is a knowledge, skills, and attitudes that must be possessed by every student, and especially Character Education that must also be embedded in the souls of students, many students do not know their character and violate good ethics. The reality that is currently happening is really sad,